Organocatalytic Group Transfer Reactions with Hypervalent Iodine Reagents - Ghosh, Manoj K.; Rajkiewicz, Adam A.; Kalek, Marcin (Synthesis, 2019)
In recent years, a plethora of synthetic methods that employ hypervalent iodine compounds donating an atom or a group of atoms to an acceptor molecule have been developed. Several of these transformations utilize organocatalysis, which complements well the economic and environmental advantages offered by iodine reagents. This short review provides a systematic survey of the organocatalytic approaches that have been used to promote group transfer from hypervalent iodine species. It covers both the reactions in which an organocatalyst is applied to activate the acceptor, as well as those that exploit the organocatalytic activation of the hypervalent iodine reagent itself.1 Introduction2 Organocatalytic Activation of Acceptor2.1 Amine Catalysis via Enamine and Unsaturated Iminium Formation2.2 NHC Catalysis via Acyl Anion Equivalent and Enolate Formation2.3 Chiral Cation Directed Catalysis and Brønsted Base Catalysis via Pairing with Stabilized Enolates3 Organocatalytic Activation of Hypervalent Iodine Reagent3.1 Brønsted and Lewis Acid Catalysis3.2 Lewis Base Catalysis3.3 Radical Reactions with Organic Promoters and Catalysts4 Summary and Outlook
Keywords: hypervalent iodine; organocatalysis; group transfer reagents; metal-free reactions; synthetic methodology